Isolation and Characterisation of Two New Lactones from the Atacama Desert-Derived Fungus Chrysosporium merdarium - Ahlam Haj Hasan; Gagan Preet; Rishi Vachaspathy Astakala; Meshari Al-Furayh; Emmanuel Tope Oluwabusola; Rainer Ebel; Marcel Jaspars (Chemistry, 2025)
The Atacama Desert, an unexplored habitat, offers intriguing potential for natural product chemistry due to the unique adaptations of microorganisms to aridity, extreme salinity, and high UV radiation. Over several years, soil samples were collected from various locations across the desert, leading to the isolation of diverse microorganisms. This paper presents the isolation and structural characterisation of two new 10-membered lactones, curvulalide B and C (3 and 4). These compounds are epimers of each other and are produced by one of the fungi isolated from the samples collected, using LC–MS and 1D and 2D NMR techniques. The compounds were tested against the ESKAPE pathogens, bovine mastitis pathogens, and Cryptococcus neoformans but were inactive against them.